2014 International Conference on Multisensor Fusion and Information Integration for Intelligent Systems (MFI) 2014
DOI: 10.1109/mfi.2014.6997687
|View full text |Cite
|
Sign up to set email alerts
|

Chinese sentiment classification using a neural network tool — Word2vec

Abstract: Sentiment classification is the main and popular task in the field of sentiment analysis. Most of the existing researches focus on how to extract the effective features, such as lexical features and syntactic features, while limited work has been done on the extraction of semantic features, which can make more contributions to sentiment classification. This paper presents a method for sentiment classification based on word2vec. Word2vec is a tool, which establishes the neural network models to learn the vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…Glove solves the problem that Word2Vec only considers words as well as local window information and ignores the statistical information of the corpus. With regarding, this study is demonstrated by skillfully using word embedding to transform news headlines into highdimensional vectors [20]. Secondly, the k-means clustering method is used to classify the news into K categories.…”
Section: Introductionmentioning
confidence: 99%
“…Glove solves the problem that Word2Vec only considers words as well as local window information and ignores the statistical information of the corpus. With regarding, this study is demonstrated by skillfully using word embedding to transform news headlines into highdimensional vectors [20]. Secondly, the k-means clustering method is used to classify the news into K categories.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies used vector representation as the feature weighting method. Unlike another study [16], Word2vec was actually used for the feature selection process by clustering features based on similarities. Besides Word2vec, other researches [3], [8], [4] also used the TF-IDF method as the feature weighting process.…”
Section: Methodsmentioning
confidence: 99%
“…First, running the sigmoid layer which determined which cell would be the output, then place the cell state through the tanh and increased the output of the sigmoid gate, so that only the part we specified was the output. Calculation of output gate with equations (5) and (6).…”
Section: 3 Lstm Layermentioning
confidence: 99%
“…However, semantic features are rarely considered in sentiment classification. Semantic features can reveal deep and implicit semantic relationships between words which can be more useful in the classification of sentiments [6]. In this study, word2vec is used in the feature extraction process.…”
Section: Introductionmentioning
confidence: 99%